Alternating pattern orientation or phase can increase the amplitude of the visual evoked potential - Ara, Jawshan; Tavakkoli, Alireza; Crognale, Michael A. (Vision research (Oxford), 2025)
•No contrast adaptation has been observed for cVEP amplitude over the 60 s period.•Alternating orientations of the grating patterns increase the amplitude of the cVEP.•Alternating orientations of the grating patterns decreased the latency of the cVEP.•Alternating phases increase cVEP amplitude for the L-M but not for the S pathway. Reversing, achromatic patterns generally produce large and characteristic evoked responses. However, pattern onsets produce large and reliable evoked potentials for chromatic stimuli, while pattern reversal responses are considerably weaker. These differences likely arise in part from the transient and sustained nature of the achromatic and chromatic pathways, respectively; contrast adaption of the sustained, chromatic pathways may also contribute to these observations, as time-averaged contrast is higher for pattern reversals than for pattern onsets. Evidence suggests chromatic pathways may also be tuned for orientation similar to achromatic pathways. Changing orientations may stimulate additional neural populations and reduce contrast adaptation’s effect on the evoked potential. We recorded responses to chromatic and achromatic patterns using both onsets and reversals, with and without alternating orientation. As a control, we included a “reversing” onset condition with a 180-degree spatial shift between presentations. Results revealed that responses binned over 6 s did not exhibit adaptation over 60 s. Chromatic onsets with alternating orientation or phase resulted in larger amplitudes and shorter latencies. Both orientation and phase changes increased chromatic onset responses for the L-M axis, but VEP amplitudes were smaller for alternating phases than for alternating orientations on the S-axis. One possible explanation is that in addition to recruiting different orientation-selective neurons, alternating phase or orientation produces motion responses, which are more prominent in L-M pathways than S pathways. Alternating the phases or orientations of the patterns likely increases the evoked response by recruiting additional neuron populations but at the cost of pathway specificity.